MOBILITY AND MICROBIALLY MEDIATED MOBILIZATION OF GOLD AND ARSENIC IN SOILS FROM TWO GOLD MINES IN SEMI-ARID AND TROPICAL AUSTRALIA - Reith F.; McPhail D.C. (My University, 2007)
The mobility and microbially mediated solubilization of Au and As in regolith materials from two Au mines in Australia, i.e., the Peak Hill Gold Mine in semi-arid New South Wales and the Hit or Miss Gold Mine in tropical northern Queensland, was studied using a combination of geochemical and microbiological techniques. Gold is highly mobile in both environments, the mobility of Au increases with increasing degree of weathering of host materials, and the resident microbiota are capable of mediating its solubilization. The results of the microcosm experiments demonstrate that the activity of microorganisms needs to be taken into account when studying the mobility and solubilization of Au in the Australian regolith. In primary, unweathered mineralization material from the Hit or Miss mine 99 wt% of Au was extracted only in the strongest final step of the sequential extractions, in concentrated aqua regia. In alteration zone material from the Peak Hill Gold Mine 80 wt% of Au was associated with the operationally defined Mn and Fe oxides. In contrast, in auriferous soils overlying mineralization at both sites 90-95 wt% of Au was associated with the operationally defined exchangeable, clay-bound and organic fractions. Microcosm experiments were incubated biologically active and inactive (sterilized) in 1:4 (w/v) aqueous slurries at 25 °C in the dark for up to 95 days. In biologically active microcosms with soils from the Peak Hill- and the Hit or Miss Gold Mines approximately 55 wt% (907 ng g-1 d.w. soil) and 20 wt% (233 ng g-1 d.w. soil) of the total Au, respectively, was solubilized during the incubation. In contrast, no or significantly lower Au concentrations were observed in biologically inactive microcosms. The mobility and microbially mediated release of As was limited at both sites and appears to be mostly controlled by abiotic adsorption and desorption on Mn- and Fe-oxides. Arsenic has a low solubility in the more mobile fractions and is mostly associated with Mn- and Fe-oxides and the residual fraction. The release of As was not elevated in biologically active compared to inactive microcosms from the Peak Hill Gold Mine. In contrast, in biologically active microcosms with samples from the Hit or Miss Mine elevated concentrations of As were detected in solution compared to the biologically inactive experiments. Crown Copyright © 2006.